Focusing on Helicobacter pylori infection in the elderly - Gong, Hang; Xu, Hui-Mei; Zhang, De-Kui (Frontiers in Cellular and Infection Microbiology, 2023)
As a confirmed carcinogen, Helicobacter pylori (H. pylori) is the main cause of inflammatory diseases of the upper digestive tract and even gastric cancer. There is a high prevalence of H. pylori infection among the elderly population, which may cause adverse clinical outcomes. Particularly noteworthy is that guidelines or expert consensus presently available on H. pylori infection overlook the management of the elderly population as a special group. A brief overview of H. pylori in the elderly is as follows. The detection of H. pylori infection can be divided into invasive and non-invasive techniques, and each technique has its advantages and shortcomings. There may be more side effects associated with eradication treatment in elderly individuals, especially for the frail population. Physical conditions and risk-benefit assessments of the elderly should be considered when selecting therapeutic strategies for H. pylori eradication. Unless there are competing factors, elderly patients should receive H. pylori eradication regimens to finally reduce the formation of gastric cancer. In this review, we summarize the latest understanding of H. pylori in the elderly population to provide effective managements and treatment measures.